Implementasi Program Pengendalian Pencemaran dan Perusakan Lingkungan Hidup di Sungai Batang Arau oleh Dinas Lingkungan Hidup Kota Padang - Fahri Septiawan; Roni Ekha Putera; Kusdarini Kusdarini (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2024)
This study aims to provide an in-depth investigation of implementing the pollution and environmental devastation management program in the Batang Arau River. The investigation is motivated by the significant levels of waste contamination in the Batang Arau River, primarily caused by industrial and home garbage. The contamination of the Batang Arau River leads to floods during the rainy season, adversely affecting public health and severely impacting the fishing industry in Padang City. In addition, the Padang City Government aims to enhance the water quality of the Batang Arau River from level IV to level II to make it suitable for tourism purposes. In order to address this issue, the Padang City Environmental Service has created a program to control pollution and environmental degradation in the Batang Arau River. The research employs Merilee S. Grindle's implementation theory and utilizes a qualitative methodology. The research findings indicate that the execution of the Environmental Pollution and Destruction Control Program in the Batang Arau River by the Padang City Environmental Service is now underway, however it has not yet reached its maximum effectiveness. This is because the program encountered various impediments, including limited funding, insufficient public awareness regarding the preservation of the Batang Arau River's ecology, and the failure to attain the program's primary benefits. Nevertheless, the program's implementation has been executed proficiently.